Thermal plasma technology applied to the inertization process of the inorganic fraction of sewage sludge generated from municipal wastewater treatment plant - Sant'Anna Junior, Alvaro Busquet de; Miranda, Felipe de Souza [UNESP]; Moreira Junior, Pedro William Paiva; Cruz, Antonio Carlos da; Essiptchouk, Alexei [UNESP]; Ferreira, Antonio; Fuji, Marcio; Petraconi, Gilberto (Iop Publishing Ltd, 2025)
This study investigates the thermal plasma pyrolysis process for inertizing the inorganic fraction of sewage sludge from municipal wastewater treatment plants. The aim is to assess its effectiveness in waste inertization. Lab-scale experiments were conducted to process the sludge thermally. Elemental composition analysis was done using x-ray fluorescence (XRF), thermogravimetry coupled with mass spectrometry (TGA-MS) and x-ray diffraction (XRD). The XRF analysis showed an initial composition of Si, Al, Fe, and Ca, corresponding to 86.8% of the inorganic matter of the sludge. TGA-MS analysis showed a significant mass loss between 200 and 650 degrees C, corresponding to organic matter volatilization, methane conversion, and dehydrogenation of polymorphic silicon. XRD analysis revealed a dried sludge crystalline structure composed mainly by SiO2, CaCO3, and AlPO4, and after plasma treatment, the remaining composition of the slag was primarily SiO2 amorphous. Mass and energy balances, considering thermodynamic equilibrium and chemical reactions, are performed. The mass balance calculations identified the most probable composition of the sludge, and energy balance calculations determined a net energy requirement of 399 kWh for plasma inertization, with an additional 300 kWh to account for furnace losses. Solubility and leaching tests confirm the inert nature of the residue. Power requirements are estimated at 700 kW for processing 350 kg h-1 of decarbonized sludge. These findings are crucial for optimizing plasma inertization processes in wastewater treatment plants. This work presents a novel approach by combining a computational prediction for an industrial-scale plant with a direct experimental assessment of the plasma treatment process.
Keywords: thermal plasma pyrolysis; sewage sludge inertization; elemental characterization; leaching and solubility tests; energy and mass balances